Yawning: role of hypothalamic paraventricular nitric oxide - Melis Maria Rosaria; Argiolas Antonio (Acta Pharmacologica Sinica, 2016)
Yawning is a phylogenetically old, stereotyped event that occurs alone or associated with stretching and/or penile erection in humans, in animals from reptiles to birds and mammals, under different conditions. Several neurotransmitters and neuropeptides are involved in its control at the central level. One of these at the level of the paraventricular hypothalamic nucleus (PVHN) is nitric oxide (NO). First, NO synthase inhibitors injected into this hypothalamic nucleus prevent yawning induced by dopamine agonists, oxytocin or N-methyl-D-aspartic acid (NMDA), which induce yawning by activating PVHN oxytocinergic neurons projecting to extra-hypothalamic brain areas. The inhibitory effect of NO synthase inhibitors was not observed when these compounds were given concomitantly with L-arginine, the precursor of NO. Second, dopamine agonists, NMDA and oxytocin given at doses that induce yawning, increase NO production in the PVHN, as determined by in vivo microdialysis. Conversely, the opiate morphine, which prevents yawning induced by dopamine agonists, oxytocin and NMDA, also prevents the increase in the paraventricular NO production induced by these compounds. Third, NO donors, such as nitroglycerin, sodium nitroprusside and hydroxylamine, induce yawning when injected into the PVHN apparently by activating oxytocinergic transmission. Since guanylate cyclase inhibitors and NO scavengers (hemoglobin) injected into the PVHN do not prevent drug-induced yawning, nor 8-Br-cGMP injected into the PVHN induces this behavioral response, it is likely that NO acts as an intracellular rather than an intercellular modulator inside the PVHN oxytocinergic neurons in which NO is formed to facilitate the expression of this phylogenetically old event by guanylate cyclase-independent mechanisms.